Competitiveness in the modern system of human capital - Makenova, G. U. (Journal of Economic Research & Business Administration, 2015)
As you know, in today’s world one of the most effective factor in socio-economic and political development is human capital. He became the main instrument of formation and development of an innovative economy and the knowledge economy, as higher today, the stage of development of the world economic system, and no State in the world could not be sustained without its high quality and robust, forward-looking economic foundation. It should be noted that one of the foundations of the new building of Kazakh society was caring for human development, which implies education of kazakhstans new formation. Тhere is a threshold determines the stage of development of the State. In a table 1 the threshold of profit is considered, opredelyayuschii stage of development of countries. According to the table above is a 2 stage of Kazakhstan and moves to stage 3, i.e. per capita GDP for 2012, 5 according to stat.kz and in 2012 the GDP growth amounted to 6%. Income threshold and the global innovation index shows which countries best embody innovative ideas into practical results. According to the settings of transition of the Republic of Kazakhstan to sustainable development for the 2005-2024. and for the achievement of the strategic objectives requires implementation of the sustainable development of the State.